An online survey on public awareness of drug clinical trials in inland cities of northern China - Wang, Li; Zhang, Ruiguang; Liu, Jingxuan; Xu, Rui; Zhao, Lili; Li, Enze; Zhang, Yurong (Frontiers in Public Health, 2024)
Objective: The aims of this survey were to investigate the public awareness of drug clinical trials (DCTs) and willingness to participate the DCTs, and provide references for propaganda and science popularization of DCTs.: A self-designed questionnaire named "an online survey questionnaire on public awareness of DCTs" was used to conduct an online survey from January to March 2022. The demographic characteristics and the response of participants to the awareness and willingness to participate the DCTs were collected. The factors affecting the public awareness of DCTs were analyzed by single factor and binary logistic regression analysis.Results: 1380 valid questionnaires were collected, and the respondents' awareness rate of DCTs was 61.1%. 13 demographic characteristics including age, gender, education, occupation, work fields, household type, marital status, city type, income, medical insurance, medical expenditure, pressure to seek medical care, financial pressure, both significantly affected the qualified rate of participants' awareness of DCTs (P< 0.001) by single factor analysis. Binary logistic regression analysis indicated that education level, work fields, city type, medical insurance, and medical expenditure affected independently the participants' awareness rate of DCTs (P< 0.001). 52.9% of the participants were willing to take part in DCTs. "to promote medical progress" (54.4%) or "believe doctors" (31.1%) were the most frequent reasons for subjects participating in DCTs.The public awareness rate of DCTs and the willingness to participate in drug clinical were significantly affected by the demographic characteristics of subjects. Thus, targeting the needs of the public, propaganda, and science popularization of DCTs should be carried out and served public health.